La psicología universitaria peruana (1870-1905) - Orbegoso-Galarza, Arturo (2025)
This brief work is about Isaac Alzamora (1850-1930) and Pedro Labarthe (1855-1905), two Peruvian teachers that contributed to the psychology of their country between 1870 and 1905.  Alzamora published in 1882 the psychology course that he gave in San Marcos University since 1872. Labarthe presented a thesis in mathematics about Psychophysics in 1902. This article examines these contributions analyzing the social and ideological context of that age.